Amine‐Responsive Disassembly of AuI–CuI Double Salts for Oxidative Carbonylation. Issue 5 (10th December 2019) - Cao, Yanwei; Yang, Jian‐Gong; Deng, Yi; Wang, Shengchun; Liu, Qi; Shen, Chaoren; Lu, Wei; Che, Chi‐Ming; Chen, Yong; He, Lin
Abstract: A sensitive amine‐responsive disassembly of self‐assembled Au I ‐Cu I double salts was observed and its utilization for the synergistic catalysis was enlightened. Investigation of the disassembly of [Au(NHC)2 ][CuI2 ] revealed the contribution of Cu‐assisted ligand exchange of N‐heterocyclic carbene (NHC) by amine in [Au(NHC)2 ] + and the capacity of [CuI2 ] − on the oxidative step. By integrating the implicative information coded in the responsive behavior and inherent catalytic functions of d 10 metal complexes, a catalyst for the oxidative carbonylation of amines was developed. The advantages of this method were clearly reflected on mild reaction conditions and the significantly expanded scope (51 examples); both primary and steric secondary amines can be employed as substrates. The cooperative reactivity from Au and Cu centers, as an indispensable prerequisite for the excellent catalytic performance, was validated in the synthesis of (un)symmetric ureas and carbamates. Abstract : Disassembly for catalysis : A sensitive amine‐induced disassembly of self‐assembled Au I ‐Cu I double salts was observed. Stimulated by the finding and understanding on this dynamic feature, a synergistic catalytic system for the oxidative carbonylation of primary and secondary amines (51 examples) to ureas and carbamates has been developed.